Responses of the Lodging Resistance of Indica Rice Cultivars to Temperature and Solar Radiation under Field Conditions - Xiaoyun Luo; Zefang Wu; Lu Fu; Zhiwu Dan; Weixiong Long; Zhengqing Yuan; Ting Liang; Renshan Zhu; Zhongli Hu; Xianting Wu (Agronomy, 2022)
Much attention has shifted to the effects of temperature and solar radiation on rice production and grain quality due to global climate change. Meanwhile, lodging is a major cause of rice yield and quality losses. However, responses of the lodging resistance of rice to temperature and solar radiation are still unclear. To decipher the mechanisms through which the lodging resistance might be affected by temperature and solar radiation, 32 rice cultivars with different lodging resistance were grown at two eco-sites on three sowing dates over a period of three years. Based on the field observation, 12 indica rice cultivars which did not lodge were selected for analysis. Significant differences were found in the lodging resistance of the indica rice cultivars at different temperature and solar radiation treatments. The results showed that temperature was the main factor that affected the lodging resistance of indica rice cultivars under the conditions of this study. With the increased average daily temperature, the lodging resistance decreased rapidly, primarily due to the significant reduction in physical strength of the culm, which was attributed to the longer and thinner basal second internode. Among the 12 indica rice cultivars, the lodging-moderate cultivar Chuanxiang 29B was most sensitive to temperature, and the lodging-resistant cultivar Jiangan was least responsive to temperature. These results suggested that rice breeders could set the shorter and thicker basal internode as the main selection criteria to cultivate lodging-resistant indica cultivars to ensure a high yield at a higher ambient temperature.